2018
DOI: 10.1088/1748-9326/aaaf21
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring multi-year macro ocean litter dynamics and backward-tracking simulation of litter origins on a remote island in the South China Sea

Abstract: Ocean litter has accumulated rapidly and is becoming a major environmental concern, yet quantitative and regular observations and exploration that track litter origins are limited. By implementing monthly sample collections over five years (2012)(2013)(2014)(2015)(2016) at Dongsha Island, a remote island in the northern South China Sea (SCS), we assessed macro ocean litter dynamics, identified source countries of individual plastic bottles, and analyzed the origins of the litter by a backward-tracking model si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 51 publications
(78 reference statements)
1
4
0
Order By: Relevance
“…This study has shown that monitoring data can be used to estimate marine debris abundance and temporal trends, and identify drivers of debris loads on shorelines within two US National Marine Sanctuaries: Olympic Coast (OCNMS) and Greater Farallones (GFNMS). Similar to other shoreline monitoring studies worldwide, marine debris in the two sanctuaries was dominated by plastic items, in particular, plastic fragments (Derraik, 2002;Thiel et al, 2013;Hong et al, 2014;Hoellein et al, 2015;Schulz et al, 2015;Hardesty et al, 2017a,b;Nelms et al, 2017;Araujo et al, 2018;da Silva et al, 2018;Ko et al, 2018;Ryan et al, 2018;Ambrose et al, 2019).…”
Section: Discussionsupporting
confidence: 74%
“…This study has shown that monitoring data can be used to estimate marine debris abundance and temporal trends, and identify drivers of debris loads on shorelines within two US National Marine Sanctuaries: Olympic Coast (OCNMS) and Greater Farallones (GFNMS). Similar to other shoreline monitoring studies worldwide, marine debris in the two sanctuaries was dominated by plastic items, in particular, plastic fragments (Derraik, 2002;Thiel et al, 2013;Hong et al, 2014;Hoellein et al, 2015;Schulz et al, 2015;Hardesty et al, 2017a,b;Nelms et al, 2017;Araujo et al, 2018;da Silva et al, 2018;Ko et al, 2018;Ryan et al, 2018;Ambrose et al, 2019).…”
Section: Discussionsupporting
confidence: 74%
“…Floating litter is sorted out in turbulent conditions induced by wave and wind, with some items more prevalent on the water surface (high-buoyancy litter) and others more susceptible to submerge into the mixing layer (low-buoyancy litter) 28,29 . Thus, highly buoyant items are more affected by the wave-driven Stokes drift and windage, which results in ejection from the oceanic accumulation zones and transport to shore and beaches 8,26,30,31 . By contrast, low-buoyancy litter would escape the wind and waves sweeping the ocean surface and have a greater likelihood of entering into the Ekman convergence to the great mid-ocean gyres [5][6][7]32 .…”
Section: An Inshore-offshore Sorting System Of Floating Littermentioning
confidence: 99%
“…Large-sized floating fishing nets often have a long underwater draft, being less affected by wind-driven transport processes sweeping the ocean surface and more likely trapped into the subtropical gyres 8 . By contrast, shapes including internal air volume (for example, empty bottles, buoys, Styrofoam crates) are especially prone to windage, showing the highest beach delivery rates 30,31 .…”
Section: Transport Pathways Of Top Itemsmentioning
confidence: 99%
“…Still, some of the highest densities of marine litter have been reported in remote islands, not only near oceanic convergence zones (730 items⋅100 m − 1 , 500 kg⋅100 m − 1 ; in Inaccesible Island) (Ryan et al, 2019), but in islands situated far away from these garbage patches (e.g. Henderson and Dongsha Islands) (Ko et al, 2018;Lavers and Bond, 2017), revealing the global magnitude of this environmental problem.…”
Section: Introductionmentioning
confidence: 99%